Enteroviral infection in patients treated with rituximab for non‐Hodgkin lymphoma: a case series and review of the literature. Issue 4 (13th October 2016) - Grisariu, S.; Vaxman, I.; Gatt, M.; Elias, S.; Avni, B.; Arad, A.; Pasvolsky, O.; Raanani, P.; Paltiel, O.
Abstract: In recent years, anti‐CD20 antibodies have been increasingly used to treat lymphoproliferative and immune disorders. Chronic viral infections are infrequently reported in patients receiving these therapies. Enteroviral infection can cause life‐threatening meningoencephalitis and other systemic chronic syndromes in immune deficient patients. We describe the clinical courses and outcomes of 6 patients from 2 tertiary care institutions who developed chronic enteroviral infection with neurological manifestations, after combined chemoimmunotherapy with rituximab for B‐cell lymphoma. We review the literature that includes 10 sporadic reported cases of chronic enteroviral meningoencephalitis attributed to rituximab therapy. It is a rare disease, and its diagnosis is often elusive. We propose that low immunoglobulin G levels are the main risk factor for developing chronic enteroviral infection and emphasize the need for a high index of suspicion, early diagnosis, and intervention in this iatrogenic and potentially fatal complication.